2017
DOI: 10.1159/000477104
|View full text |Cite
|
Sign up to set email alerts
|

Age and Outcome in Gastrointestinal Cancers: A Population-Based Evaluation of Oesophageal, Gastric and Colorectal Cancer

Abstract: Background: With demographic changes and partial representativeness of randomized studies the question arises which results are achieved in the treatment of the elderly. The objective was to analyse population-based data on gastrointestinal cancers in terms of age. Methods: Analyses included data of the Munich Cancer Registry, i.e. 4,014, 10,127 and 42,809 invasive oesophageal, gastric and colorectal cancer patients, respectively, which were diagnosed between 1998 and 2014. Tumour characteristics and outcome w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 20 publications
2
13
0
Order By: Relevance
“…The discrepancy between the level of gene transcripts and protein is quite a frequent occurrence [ 29 ], previously observed for our patients with respect to expression of immunosuppressive IL-4 and IL-13 [ 22 ]. The phenomenon is explained by varying half-lives of mRNA and protein as well as by various posttranslational modifications which may further increase protein stability [ 29 ]. IL-32 expression has been repeatedly shown to be regulated by microRNAs [ 30 , 31 ], known to affect gene expression at transcriptional and/or translational level [ 32 ].…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…The discrepancy between the level of gene transcripts and protein is quite a frequent occurrence [ 29 ], previously observed for our patients with respect to expression of immunosuppressive IL-4 and IL-13 [ 22 ]. The phenomenon is explained by varying half-lives of mRNA and protein as well as by various posttranslational modifications which may further increase protein stability [ 29 ]. IL-32 expression has been repeatedly shown to be regulated by microRNAs [ 30 , 31 ], known to affect gene expression at transcriptional and/or translational level [ 32 ].…”
Section: Discussionsupporting
confidence: 51%
“…IL-32 expression has been repeatedly shown to be regulated by microRNAs [ 30 , 31 ], known to affect gene expression at transcriptional and/or translational level [ 32 ]. In fact, it has been suggested that transcriptomic and proteomic data should be treated as separate source of information [ 29 ]. In case of our study, the discrepancy might be associated with uncertainty of detected IL-32 isoforms.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the reliability of the research results is increased when standards are followed (including the specific disease of the patient population, similar approaches to treatment protocols, similar staging and specific age ranges), according to https://clinicaltrials.gov/ct2/about-studies/learn (last accessed November 2018). As an example, recent studies of colorectal cancer (CRC) have demonstrated that careful and effective patient selection can lead to many useful conclusions for both clinical trials and therapeutic approaches 2 3. It is noteworthy that personal demographic characteristics have an effect on participation in biomedical research.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, no reports of OLS in gastric cancer patients were found in a search of the Japanese literature (on Ichushi) despite a similar number of gastric and colorectal cancer patients in Japan. Second, the faster progression and worse prognosis of gastric cancer may make it less likely for patients to reach the dose-limiting toxicity before experiencing progressive disease [27]. Third, XELOX (capecitabine+oxaliplatin) is used more commonly in gastric cancer than FOLFOX (5-fluorouracil+folinic acid+oxaliplatin), which is frequently used in colon cancer.…”
mentioning
confidence: 99%